Fetal outcome in maternal near miss, retro-prospective study at tertiary centre - Lewis, Preeti F.; Gundaiah, Bindu; Bavdekar, Nitin B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Women are not dying because of diseases we cannot treat. They are dying because societies are yet to decide that their lives are worth saving. The statement completely comprises the unawareness of the importance of maternal health existing in society. As a result of which, there is still a lag in maternal health progression. As a part and parcel, fetal health is compromised giving rise to poor fetal outcomes. Studying fetal outcomes in such near-miss cases establishes a relationship between them. Methods: A retro-prospective observational study, conducted in the Department of Obstetrics and Gynaecology. Study involves all women who are very ill pregnant or recently delivered women who nearly died but survived a complication during pregnancy, childbirth, or within 42 days of termination of pregnancy and their fetal outcome during study period of 18 months. Results: In a study of 3604 deliveries, MNM cases were 107 births. The MNM IR was 30/1000 live births, and the most common determinant leading to near-miss is hypertensive disorders followed by hemorrhage. Total perinatal mortality was 439 with a PNMR of 125/1000 births. Among the 107 near-miss cases perinatal mortality was seen in 29 pregnancies contributing to 6.6% of the total PNMR. Conclusions: Fetal outcome improves with improvement in maternal health, as the maternal morbid condition is directly proportional to fetal outcome. This requires identifying and filling up gaps in the maternal health system to improve women’s health, further reducing fetal morbid conditions and consumption of neonatal resources.